ANALISIS BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN DI PASAR MODERN ALFAMART KOTA BIMA - Setiawan, Rudi; Ernawati, Sri (STAI Darul Qalam Tangerang, 2023)
In the current era of globalization, there are many places to sell various products, plus the presence of minimarkets with the name Alfamart has mushroomed in Indonesia. This study aims to determine the effect of the marketing mix on purchasing decisions at Alfamart Kota Bima. This type of research is associative with data collection techniques using observation, literature study and questionnaires with a Likert scale. The total population in this study were all consumers who had bought at Alfamart with a sample of 50 people. The data analysis technique used validity test, reliability test, simple regression, determination test, correlation test and t test. The results of this study where it can be stated that the marketing mix has a positive and significant effect on purchasing decisions at Alfamart Bima City